Oxygen diffusion in single crystal barium titanate. Issue 19 (21st May 2015) - Kessel, Markus; De Souza, Roger A.; Martin, Manfred
<x xml:space="preserve">Abstract</x> Oxygen isotope experiments reveal a surface space-charge layer and a migration enthalpy of oxygen vacancies of 0.7 eV.